Electrochemical studies and potential anticancer activity in ferrocene derivatives. Issue 2 (17th January 2017) - Realista, Sara; Quintal, Susana; Martinho, Paulo N.; Melato, Ana I.; Gil, Adrià; Esteves, Teresa; Carvalho, Maria de Deus; Ferreira, Liliana P.; Vaz, Pedro D.; Calhorda, Maria José
Abstract: Several ferrocene derivatives (five mononuclear and two binuclear), including the new N -( p -chlorophenyl)-carboxamidoferrocene (1 ), were synthesized and their anticancer activity investigated. Two of them, 3 and7, bearing a benzimidazole backbone were the most active against HeLa cells achieving IC50 values of ~5 μM along with4 with a dipyridylamine ligand (~6 μM). Complex6, also with a benzimidazole backbone, displayed slightly higher values (~11 μM). Cyclic voltammetry studies show that while the non-cytotoxic ferrocene derivatives1, 2, and5 follow a ferrocene-based redox behavior, derivatives3, 4, 6, and7 exhibit a more complex mechanism. These complex mechanisms are consistent with a more effective cytotoxic activity. Mössbauer spectroscopy parameters reflect a very small influence of the substituents. Abstract :